Bilateral Symmetrical Diabetic Bullae - Murthy Pendyala S; Rajagopal Ramachandran; Kar P K; Neog Lipika (Wolters Kluwer Medknow Publications, 2004)
Several types of cutaneous lesions are described in association with diabetes. Spontaneous bulla is a characteristic type of skin lesion that is rarely seen. Only about 100 cases have been described in the literature. We report an unusual case where the lesions developed spontaneously, on both great toes in a symmetrical distribution.